Nepal : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix reviews agricultural productivity in Nepal and examines its links at the regional and aggregate levels to the amounts of available inputs such as chemical fertilizers, irrigation water, and improved seeds, as well as rainfall, rural credit, and foreign aid. The paper highlights factors that are statistically correlated with agricultural productivity and, as importantly, those that are not. The paper examines causes for the recent export slowdown. The bottom-heavy civil service structure is also described.